Analysis of the Prevalence and Severity of Dysregulated Bone Mineral Homeostasis in Nondialyzed Chronic Kidney Disease Patients - Patel, Digishaben D.; Vachhani, Uday; Rajput, Ajay; Raghavani, Pratik; Parchwani, Deepak N.; Dholariya, Sagar (Journal of Laboratory Physicians, 2021)
Background Progressive loss of kidney function in chronic kidney disease (CKD) leads to altered mineral homeostasis, reflected by the imbalance in calcium and phosphorus, and has been associated with progression of renal failure.Aims The aim of this study was to investigate CKD-mineral bone disorder (CKD-MBD)-associated candidate variables and its relationship with parathyroid hormone (PTH), as well as to quantify the prevalence of CKD-associated mineral disturbances in nondialyzed CKD patients.Materials and Methods This cross-sectional analytical study included 124 CKD patients and 157 control participants. Blood samples were analyzed for serum total calcium, phosphorus, PTH, electrolytes, and other hematological/hemodynamic parameters by standard methods. Suitable descriptive statistics was used for different variables.Results The 124 patients had a mean age of 50.2 ± 7.8 years with male to female ratio of 1.58; majority of patients had stage 3 CKD (40.32%), and the most common comorbid conditions were diabetes mellitus (n = 78 [62.9%]) and hypertension (n = 63 [50.8%]). A high prevalence of mineral metabolite abnormalities was observed in a patient cohort; overall prevalence of hyperparathyroidism was found in 57.25% patients, hypocalcemia in 61.29%, and hyperphosphatemia in 82.25% patients. Prevalence of abnormal homeostasis (with regard to total calcium, phosphate, and PTH) increased progressively with the severity of disease (analysis of variance; p < 0.05). Significant differences in the mean values of total calcium, phosphorus, alkaline phosphatase, and PTH were seen compared with healthy participants (p < 0.0001). Furthermore, there was a significant positive correlation between serum PTH with serum phosphorous (R2: 0.33; p < 0.0001), serum creatinine (R2: 0.084; p < 0.0259), serum potassium (R2: 0.068; p < 0.0467), and a significant negative correlation with serum total calcium (R2: 0.37; p < 0.0001).Conclusions CKD patients are at risk of or may already have developed secondary hyperparathyroidism apparent from PTH-linked derangements in mineral metabolism in predialysis CKD patients. These abnormalities start in early stages of CKD and worsen with disease progression. This accentuates the significance of early recognition of mineral bone disorder, understanding its pathophysiological consequences and scheduling necessary interventions/management strategies to protect the CKD patients from a plethora of complications.
Keywords: chronic renal insufficiency; calcium; phosphorus; PTH